Pendataan Mitra Produk Herbal CV. Rinjani Tirta Lombok Timur Berbasis Geographic Information System (GIS) - Imam Fathurrahman; Lalu Muhammad Samsu (Fakultas Teknik Universitas Hamzanwadi, 2021)
The purpose of this research is to facilitate consumers in finding partners who sell herbal products from CV. Rinjani Tirta which is in East Lombok.Where the company is engaged in herbal products and has more than 86 products. In fact, it is one of the companies that has obtained a BPOM permit in East Lombok and has been recommended by the BPOM to continue to participate in activities held by the BPOM and the government related to permits, seminars, and product exhibitions The use of a Geographic Information System (GIS) can help provide information on the data collection of partners working with companies. The author researched with several stages, namely information gathering, planning, development of initial product formats, initial product trials, field trials, product revisions, and final results. The location of the research is CV. Rinjani Tirta located in the village of Ajani Timur, Suralaga subdistrict. The results of this study are very helpful CV. Rinjani Tirta in promotion and gathering information about partners and areas that have been widely spread and make it easier for consumers to find herbal products. Besides, to streamline the work of employees and of course indirect promotions from partners.